NONLINEAR PROPERTIES OF BARIUM TITANATE CERAMICS - IVAYLO LAZAROV; ANKA ZHEGLOVA (Journal of Engineering Studies and Research)
The materials based on barium titanate have nonlinear dependence of polarization on the intensity of the electrical field. The properties of those materials are used when different automation elements such as primary converters, phase regulators for low and high frequencies, sensors, modulators etc. are derived. Ceramics based on barium titanate (BaTiO3) alloyed with H3BO3 and Bi2O3 have been derived and researched. The influence of the temperature of sintering on the values of the dielectric permittivity on the structural properties has been determined. The influence of the quantity of the added material on the temperature dependencies and the non-linear properties of the ceramics have been analyzed. Both legation additives decrease the sintering temperature. However, the values of the dielectric permittivity decrease while the non-linear properties of the doped barium titanate (BaTiO3) improve. The coefficient of non-linearity reaches its maximum for the H3BO3 composites, synthesized at temperature of 1100 oC.